INVESTIGATING THE ROLE OF COGNITIVE AND SOCIAL SKILLS IN TEACHER SELF-REGULATION AND IDENTIFYING THE MECHANISMS FOR THE EMERGENCE OF NEW SKILLS - Kosayeva, Aytakin; Gurbanova, Aygun (Revista Gênero e Interdisciplinaridade, 2025)
The teaching profession is a field of activity that requires high emotional and social responsibility. For this reason, the prevalence of emotional burnout syndrome among teachers poses a threat to both individual well-being and the quality of instruction. This article analyzes the causes of emotional burnout in the pedagogical environment, its psychological mechanisms, and contemporary methods of combating it. In this context, emotional burnout syndrome jeopardizes both individual well-being and the quality of instruction in the pedagogical setting. The article scientifically analyzes the causes of emotional burnout, its psychological mechanisms, and modern strategies for intervention.The findings conclude that the main prerequisites for preventing emotional burnout include strengthening teachers’ emotional self-awareness, stimulating their creative potential, and enhancing social and organizational support. The article demonstrates that ensuring emotional well-being in the pedagogical environment is possible not only through individual psychological interventions but also through systemic, values-based approaches.